2010
DOI: 10.1007/s11250-010-9596-0
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition and in sacco degradability of four varieties of cassava leaves grown in Southwestern Nigeria in the rumen of sheep

Abstract: The nutritive value of leaves of four varieties of cassava (MS 6, TMS 30555, Idileruwa and TMS 30572) were studied through analysis of their chemical components and degradability of their dry matter (DM) and crude protein (CP) in the rumen of sheep. Results of the chemical analyses showed that the leaves of the four varieties contained different proportions of organic matter which was significantly (P < 0.05) highest in TMS 30572 with value of 935 g/kg DM, while CP (gram per kilogramme DM) was significantly hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…The ADFI, ADG, and FCR are important indicators of animal feed value. Here, goat diets containing cassava foliage promoted growth, consistent with effects seen for ruminants in West Africa [9,15]. However, it has also been reported that cassava leaves contain antinutrients (e.g., hydrogen cyanide [HCN]), which may affect animal health and growth [27].…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The ADFI, ADG, and FCR are important indicators of animal feed value. Here, goat diets containing cassava foliage promoted growth, consistent with effects seen for ruminants in West Africa [9,15]. However, it has also been reported that cassava leaves contain antinutrients (e.g., hydrogen cyanide [HCN]), which may affect animal health and growth [27].…”
Section: Discussionsupporting
confidence: 77%
“…In less developed countries and regions lacking high-quality feed, adding cassava foliage to animal diets has a positive effect on digestion, growth, and gastrointestinal tract development [ 9 , 10 , 11 , 12 , 13 , 14 ]. However, for each ruminant species, there is an optimum percentage of cassava foliage in the diet to maximize growth; for example, the ideal is 75% for sheep, 60% for West African Dwarf goats, 50% for pigs, and 5% for geese [ 9 , 10 , 13 , 15 ]. Based on the above studies, cassava foliage should support goat production in tropical China, but the ideal ratio of cassava foliage supplementation remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…; Oni et al . ). The CP content of the experimental diets was planned to be 12% of DM to provide 1.5 times CP requirement for maintenance (National Research Council (NRC) ) and the recommended level for fattening ruminants (NARO ).…”
Section: Methodsmentioning
confidence: 97%
“…The CF contained higher CP but lower ruminal degradable protein than AH (Oni et al . ; Miranda et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…Onwuka & Akinsoyinmu [6] stated that the presence of mineral elements in animal feed is vital for the animals' metabolic process. This goes to buttress the idea that common salt (NaCl) supplementation is ideal in goat and sheep where browse is the sole feed [7]. The use of herbaceous forage legumes in livestock production systems for ruminants in the tropics has increased as the legumes are rich in protein which is usually the most limiting nutrient in tropical animal diets [8].…”
Section: Introductionmentioning
confidence: 99%